Interview with Marilyn Ramirez [Home Economics student], October 18, 1968 (1969)
Interview with Home Economics student about student projects in the department. The interview was recorded during half-time of a Cal Poly football game. [00:00:02] Interviewer introduces Junior major in Home Economics, Marilyn Ramirez [00:00:20] Ramirez begins to list projects they have worked on recently, Operation Hand Class donations to Vietnam, and flood recovery aid [00:01:15] Interviewer brings up less publicized events, like the Nursery School project that some girls have been working on [00:01:45] Ramirez discusses some students individual programs or senior projects [00:02:20] Ramirez talks about grass roots night education program [00:02:40] Interviewer asks why students tackle such difficult, community services projects rather than easier senior projects that could be completed in the library [00:03:55] Interviewer talks about War moratorium that happened in the past week and the idea of community concern [00:04:40] Interviewer begins to wrap up the interview